Gender differences in school achievement: The role of self-regulation - Weis, Mirjam; Heikamp, Tobias; Trommsdorff, Gisela (Frontiers in Psychology, 2013)
This study examined whether different aspects of self-regulation (i.e., emotion and behavior regulation) account for gender differences in German and mathematics achievement. Specifically, we investigated whether higher school achievement by girls in comparison to boys can be explained by self-regulation. German and mathematics achievement were assessed in a sample of 53 German fifth graders (19 boys, 34 girls) using formal academic performance tests (i.e., reading, writing, mathematics) and teachers’ ratings (i.e., grades in German and mathematics). Moreover, teachers rated children’s behavior regulation using the Self-Control Scale (SCS-K-D). Children’s self-reported strategies of emotion regulation were assessed with the Questionnaire for the Measurement of Stress and Coping in Children and Adolescents (SSKJ 3-8). Age and intelligence (CFT 20-R) were included as control variables. Analyses of mean differences showed that girls outperformed boys in German achievement and behavior regulation. Regression analyses, using a bootstrapping method, revealed that relations between gender and German achievement were mediated by behavior regulation. Furthermore, we found a suppression effect of behavior regulation on the relation between gender and mathematics achievement: boys’ mathematics achievement was underestimated when the analyses did not control for behavior regulation. We discuss these results from a developmental perspective and within the theoretical framework of self-regulation and achievement.